Test-retest reliability and criterion validity of a new Taekwondo Anaerobic Intermittent Kick Test - Tayech, A.; Mejri, M. A.; Chaabene, H.; Chaouachi, M.; Behm, D. G.; Chaouachi, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to determine the relative and absolute test-retest reliability and criterion validity of a new Taekwondo Anaerobic Intermittent Kick Test (TAIKT). METHODS: Twenty Tunisian elite Taekwondo athletes participated in this study (15 males and 5 females). Participants performed the TAIKT and the Running-based Anaerobic Sprint Test (RAST), twice (test and retest), on separate occasions three-week apart. Peak heart rate (HRpeak), blood lactate concentration [La?], and rating of perceived exertion (RPE) were measured during each session. RESULTS: There was no significant difference between the test and retest of TAIKT and RAST for all performances and physiological variables, except for the absolute mean power (Pmean) of RAST. Test-retest results showed that the TAIKT and RAST were reliable. All TAIKT and RAST parameters had an ICC>0.90, SEM<5%, with the smallest worthwhile change slightly higher than SEM, with very small limits of concordance. Strong significant correlations were found between TAIKT and RAST parameters (Ppeak (r=0.81; r=0.70), Pmean (r=0.72; r=0.60) in (W and W·Kg-67 respectively), fatigue index (r=0.81), [La?] (r=0.89) and RPE (r=0.78) at P<0.01, and HRpeak (r=0.55, at P<0.05)). CONCLUSIONS: The findings showed that the TAIKT can be considered as a valid and reliable specific test for assessing anaerobic power of Taekwondo athletes.